Green algae Caulerpa racemosa inhibit proliferation and promote apoptosis in human HT-29 colon cancer by suppressing PI3K/AKT pathway. - Permatasari, Happy Kurnia; Amalia, Nurlinah; Wahyu Sulistomo, Hikmawan; Wantri Anita, Kenty; Khotimah, Husnul; Kurniawan, Rudy; Nurkolis, Fahrul (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Colon cancer is a malignancy of the gas trointestinal which is one of the most common causes of death worldwide. Tumorigenesis involved oncologic pathway such as PI3K/AKT as the common pathway with the challenges is ther apy resistance. Therefore, an alternative colon cancer treat ments is needed that comes from biological resources such as sea grapes. Objective: This study aims to determine anticancer po tency of hexane extract from sea grapes (Caulerpa race mosa) on HT-29 cell line colon cancer based on suppress ing PI3K/AKT pathway. Method: The study was conducted in vitro using the ex tract of Caulerpa racemosa at concentrations of (0, 400, 800, and 1.200) µg/mL on the HT-29 cell line based on the level expression of p-akt related to PI3K/AKT pathway, cleaved caspase 3 related to apoptosis, and viable cells related to proliferation. Results: The research results was found that the hexane extract of Caulerpa racemosa decreased the expression level of p-akt (Kruskal wallis, p=0,027), increased the cleaved caspase 3 (Kruskal wallis, p=0,016), and decreased the viable cells (Kruskal wallis, 24 and 48 hours: p=0,024 and 0,034). Conclusion: Caulerpa racemosa hexane extract can inhibit colon cancer cells growth by suppressing PI3K/AKT pathway based on inhibition proliferation and induce apoptosis.